2000
DOI: 10.1021/ol9902935
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Bromination of Organic Substrates by Tetrabutylammonium Bromide Promoted by V2O5−H2O2:  An Environmentally Favorable Synthetic Protocol

Abstract: [reaction: see text] Vanadium pentoxide very effectively promotes the bromination of organic substrates, including selective bromination of some aromatics, by tetrabutylammonium bromide in the presence of hydrogen peroxide; mild conditions, high selectivity, yield, and reaction rate, and redundancy of bromine and hydrobromic acid are some of the major advantages of the synthetic protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(48 citation statements)
references
References 12 publications
1
44
1
2
Order By: Relevance
“…[39] When a sufficiently large amount of vanadium(V) oxide is used (50 mol %), no additional acid is required to ensure complete halogenation, since V 2 O 5 itself ensures an acidic media (pH 2.1). [40,41] Similar results were obtained when flavone and aurone derivatives were brominated. The bromination of ketones in the presence of V 2 O 5 leads to enolization through chelation of a 1,3-dicarbonyl compound.…”
Section: Vanadium and Molybdenum Complexes As Functional Mimics Of Vasupporting
confidence: 66%
See 1 more Smart Citation
“…[39] When a sufficiently large amount of vanadium(V) oxide is used (50 mol %), no additional acid is required to ensure complete halogenation, since V 2 O 5 itself ensures an acidic media (pH 2.1). [40,41] Similar results were obtained when flavone and aurone derivatives were brominated. The bromination of ketones in the presence of V 2 O 5 leads to enolization through chelation of a 1,3-dicarbonyl compound.…”
Section: Vanadium and Molybdenum Complexes As Functional Mimics Of Vasupporting
confidence: 66%
“…H 2 O 2 can also act as a nucleophile, and it was reported that peroxides are formed together with iodohydrines in the iodination of cyclohexene (40). [110] Vicinal iodoperoxyalkanes were isolated together with some iodohydrines when different alkyl hydroperoxides-and even H 2 O 2 -were used for the oxidative iodination (Scheme 29).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Product 16a is an important precursor for flavonoids (cf. vitexin) (30). a-bromination of acetophenone 17, a deactivated aromatic compound, to the corresponding a-bromo acetophenone 17a in high yield has also been successful.…”
Section: Screening Of Reaction Conditionsmentioning
confidence: 99%
“…Our earlier work on peroxoborate (29) and oxidative bromination of aromatics (30) suggested that the peroxoborate intermediate generated in situ would enable bromide oxidation in presence of an acid. The fact, that Br 3 is formed in this process has been ascertained from an independent experiment wherein Br was oxidized by the present methodology in the absence of any organic substrate but in the presence of tetrabutylammonium chloride and three equivalents of KBr leading to nearly quantitative isolation of tetrabutylammonium tribromide (TBATB) (98% yield) (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…1 Organic tribromide salts as mild reagents are good candidates for this selective conversion, because they are not only stable, crystalline solids, and relatively soluble in most organic solvents but also can be handled more conveniently than liquid bromine and can be used successfully for this purpose. Although they are used as brominating agents of aromatic rings, 2 α-bromination of ketones, [3][4][5][6] and ketals, 3,7 electrophilic addition, 3,4,[8][9][10][11][12][13][14] and substitution, 4,13,[15][16][17][18][19] they are also used as catalyst for the oxidation of aromatic aldehydes to carboxylic acids 20 or ω-bromoesters, 21 and dialkyl and alkyl aryl sulfides to sulfoxides, 22 protection of carbonyl, 23 and hydroxyl groups, 24 cleavage of ethers and dithioacetals 25 and conversion of thioamides into amides. 26 They can also be applied in the synthesis of heterocyclic ring systems such as aziridines 27 and benzothiazoles.…”
Section: Introductionmentioning
confidence: 99%